Interplay between microstructural evolution and tribo-chemistry during dry sliding of metals - Philipp G. Grützmacher; Sebastian Rammacher; Dominic Rathmann; Christian Motz; Frank Mücklich; Sebastian Suarez (Friction, 2019)
Abstract Understanding the microstructural and tribo-chemical processes during tribological loading is of utmost importance to further improve the tribological behavior of metals. In this study, the friction, wear and tribo-chemical behavior of Ni with different initial microstructures (nanocrystalline, bi-modal, coarse-grained) is investigated under dry sliding conditions. In particular, the interplay be-tween frictional response, microstructural evolution and tribo-oxidation is considered. Friction tests are carried out using ball-on-disk experiments with alumina balls as counter-bodies, varying the load between 1 and 5 N. The microstructural evolution as well as the chemical reactions beneath the samples’ surface is investigated by means of cross-sections. The samples with finer microstructures show a faster run-in and lower maximum values of the coefficient of friction (COF) which can be attributed to higher oxidation kinetics and a higher hardness. It is observed that with increasing sliding cycles, a stable oxide layer is formed. Furthermore, initially coarse-grained samples show grain refinement, whereas initially finer microstructures undergo grain coarsening converging towards the same superficial grain size after 2,000 sliding cycles. Consequently, the experimental evidence supports that, irrespective of the initial microstructure, after a certain deformation almost identical steady-state COF values for all samples are achieved.